2015
DOI: 10.1159/000374099
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology and a Rational Basis of Therapy

Abstract: Portal hypertension is a common complication of chronic liver disease. Its relevance comes from the fact that it determines most complications leading to death or liver transplantation in patients with cirrhosis of the liver: bleeding from esophageal or gastric varices, ascites and renal dysfunction, sepsis and hepatic encephalopathy. Portal hypertension results from increased resistance to portal blood flow through the cirrhotic liver. This is caused by two mechanisms: (1) distortion of the liver vascular arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Several studies have demonstrated that celecoxib could efficiently ameliorate portal hypertension and fibrosis in several animal models [ 6 , 12 , 13 , 34 ]. Octreotide is indicated for the management of bleeding from gastroesophageal varices in patients with cirrhosis [ 14 ]. The regime to combine celecoxib with octreotide was firstly investigated in the rat model with cirrhotic portal hypertension in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that celecoxib could efficiently ameliorate portal hypertension and fibrosis in several animal models [ 6 , 12 , 13 , 34 ]. Octreotide is indicated for the management of bleeding from gastroesophageal varices in patients with cirrhosis [ 14 ]. The regime to combine celecoxib with octreotide was firstly investigated in the rat model with cirrhotic portal hypertension in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, such effect is related to its inhibition of intrahepatic angiogenesis and epithelial-to-mesenchymal transition of hepatocytes [ 12 , 13 ]. Somatostatin (SST) and its analogue octreotide are widely used for the management of bleeding from gastroesophageal varices in patients with cirrhosis [ 14 ]. It is notable that octreotide could inhibit angiogenesis in HCC and in the early stage of portal hypertension induced by partial portal vein ligation [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…All transfusion management plans should be handled with great caution, and transplant physicians should very carefully evaluate the effects of increases or decreases of transfusions [60][61][62] . A response time lag due to endothelial injury and permeant breakdown should be considered in LC recipients with long-term PH [63][64][65] . Adequate hydration is also required; dehydration should be avoided because of these patients' peculiar hemodynamics.…”
Section: Management Of Lt Recipients With Advanced Lcmentioning
confidence: 99%
“…Peculiar hemodynamics in advanced cirrhosis permeant breakdown, and systemic arterial pressure may be effected even by body motion [63][64][65] . Diuretics (e.g., furosemide and potassium-conserving diuretics) and a water-clearance mediator (e.g., tolvaptan) are available [71] .…”
mentioning
confidence: 99%
“…The cause of these disorders may be the flow of vasodilator substances ( e.g ., glucagon, endocannabinoid, atrial natriuretic peptide, bacterial endotoxin) through the network of portosystemic shunts, as well as increased production of topical vasodilators by endothelium, such as NO, carbon monoxide, PGI2, endothelium-derived hyperpolarizing factor, adrenomedullin, hydrogen sulfide. Furthermore, in spite of increased circulating levels of endogenous vasoconstrictors (noradrenaline, ET-1, angiotensin II), vascular sensitivity to them is significantly reduced[41]. …”
Section: The Systemic and Splanchnic Adaptive Response Of Vascular Bementioning
confidence: 99%